Energy Efficient Homes: Water Heaters - Wendell A. Porter; Hyun-Jeong Lee; Kathleen C. Ruppert; Randall A. Cantrell (EDIS)
Water heaters are the third largest energy expense in your home. This revised 5-page fact sheet describes factors to consider when purchasing and lists the various choices available. Written by Wendell A. Porter, Hyun-Jeong Lee, Kathleen C. Ruppert, and Randall A. Cantrell, and published by the UF Department of Family Youth and Community Sciences, August 2011.